MEASURING THE FACTORS IMPACTING CONSUMERS’ PURCHASE INTENTIONS OF FAST FASHION - Negm, Eiman Medhat (PEOPLE: International Journal of Social Sciences, 2019)
This study investigates what factors influence fast fashion purchase intentions. This study focuses on: (1) hedonic and rational clothing attributes; (2) media exposure to the fashion world: (3) attitude, subjective norm, and perceived behavioral control based on TPB. This study tries to answer the following research questions: Does hedonic and rational factors impact attitude formation towards fast fashion purchasing intentions? Do media communication trigger consumers’ attitude formation, subjective norms and perceived behavior control? Do attitude, subjective norm, and perceived behavioral impact consumers’ fast fashion purchasing intentions? This study used a quantitative research approach. This study used the SPSS to analyze 400 administrated questionnaires. Results showed a significant, positive, and strong relationship between hedonic shopping elements and attitude formation. The rational shopping elements proved to be insignificant when it comes to attitude formation towards fast fashion. This study indicated that purchase intentions for fashion apparel are supported by media communication. Media communication impacts attitudes toward the behavior, subjective norms, and perceived behavioral control in a significant, positive and strong manner. Finally, the analysis showed that attitudes toward the behavior, subjective norms, and perceived behavioral control have a significant, positive and strong relationship with fast fashion purchasing intentions.